PEDAGOGICAL APPLICATIONS OF TEACHING ENGLISH VOCABULARY - Karimova Umida; Mehmonova Feruza (Web of Journals Publishing, 2023)
This article provides guidance on teaching expressions that have several meanings and provides practice exercises. This section discusses how individuals who are learning a foreign language may err by employing expressions that aren't appropriate in that language.
Keywords: еxрrеssiоn, metaphors, соmрlеtеlу ораquе, indiсаtiоns.